CD56-positive lymphocyte infiltration in relation to human papillomavirus association and prognostic significance in oropharyngeal squamous cell carcinoma - Wagner, Steffen; Wittekindt, Claus; Reuschenbach, Miriam; Hennig, Ben; Thevarajah, Mauran; Würdemann, Nora; Prigge, Elena-Sophie; Knebel Doeberitz, Magnus von; Dreyer, Thomas; Gattenlöhner, Stefan; Klussmann, Jens Peter (International journal of cancer, 2016)
Human papillomavirus (HPV)-related squamous cell carcinoma of the oropharynx (OSCC) are clinical and biological distinct from their HPV-unrelated counterparts. Patients with HPV-related OSCC display improved prognosis and therefore we investigated possible immune cell infiltrations associated with this tumor phenotype. We retrospectively analyzed a randomly selected cohort of 140 OSCC for presence of immune cells and HPV by immunohistochemistry and PCR followed by bead-based hybridization (Luminex technology). HPV prevalence was 24.3% as determined by positive staining of p16INK4a and detection of high risk HPV-DNA. We found significantly higher numbers of CD56 positive (CD56+) cells in tumor and surrounding microenvironment in HPV-associated compared to HPV-negative OSCC (t-test: p = 0.004 and p = 0.002). For the entire cohort presence of CD56+ cells was associated with increased overall survival independent from HPV (Kaplan-Meier: p = 0.002; Cox regression: p = 0.042). Presence of CD56+ cells also correlated with a better outcome in HPV-negative and especially in HPV-negative OSCC with alcohol consumption ≤2 standard drinks per day (Kaplan-Meier: p = 0.05 and p = 0.003). Immunofluorescence localization of granular Granzyme B (GZMB) within CD56+ cells and coexpression of CD16 and CD56 suggests that detected CD56+ cells mainly represent cytotoxic Natural Killer (NK) cells. The fraction of potentially cytotoxic NK cells was significantly higher in HPV-associated compared to HPV-negative OSCC (Mann-Whitney-U-Test: p = 0.011). The elevated abundance and activity of cytotoxic NK cells in OSCC with HPV driven carcinogenesis might contribute to favorable outcome in HPV-related OSCC.